One new species and one new record of Nephelomilta Hampson (Lepidoptera, Erebidae, Arctiinae) from Southeast Asia - Bayarsaikhan, Ulziijargal; Mustafa, Bilal; Kwon, Hyung Wook; Bae, Yang-Seop (Zootaxa, 2023)
A new species, Nephelomilta vinhphuciensis sp. nov. is described from Vietnam (Vinh Phuc province) along with the nominate species, N. sumatrana (van Eecke, 1927) newly recorded from Thailand (Ranong province). Illustrations of adults and male genitalia of the examined species are presented.